CLINICO-PATHOLOGICAL EVALUATION OF PATIENTS WITH ABNORMAL UTERINE BLEEDING - Anwar, Rabiah; Jamal, Nighat; Anwar, Sobia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate clinical spectrum in women of different age groups presenting with menstrual irregularities without any organic pelvic pathology and to correlate clinical and pathological aspects in these women. Study Design: Cross sectional analytical study. Place and Duration of Study: Department of Gynecology and Obstetrics, Pakistan Naval Ship (PNS) Shifa Hospital, Karachi from Feb 2018 to Jan 2019. Methodology: Complete history, clinical examination, laboratory investigations, pelvic scan and endometrial biopsy of patients were done to diagnose abnormal uterine bleeding without organic (structural) pathology. Evaluation of clinical spectrum of menstrual irregularities in different age groups and histopathology of their endometrial samples was done. Results: A total of 184 cases were included. Mean age of patients presented with abnormal uterine bleeding was 38.49 ± 9.158. It was most common in the age group 41-50 years (41.84%) followed by 31-40 years (29.34%). Majority of them were multipara 146 (79.34%). The most common presentation was heavy menstrual bleeding (50.54%) followed by irregular menstrual bleeding (17.93%). Histopathology of endometrium revealed proliferative (41.30%) followed by hyperplastic (27.71%) and secretory (21.19%) pattern. 3.26% had atrophic endometrium and 1.63% cases had endometrial carcinoma. Conclusion: In conclusion, 41-50 year age group was mostly affected by abnormal uterine bleeding. Their menstrual pattern was heavy, irregular, frequent and prolonged. Proliferative and hyperplastic pattern of endometrium was observed in these patients.